Obligations of non-state parties to the Rome Statute to cooperate with the international criminal court : a look at Libya and the Sudan - Nzioki, Benedict Munene (Strathmore University, 2016)
For the longest period in the history and development of International Law, the main subjects of it were states, in and of themselves. However, with the coming into force of the Rome Statute of the International Criminal Court (ICC) in July of 2002, a great and substantive shift was experienced in this area of law. The Rome Statute made individuals the primary subjects of ICL; they could be held jointly and personally liable for crimes such as: crimes against humanity, genocide, war crimes and the last envisioned crime is the crime of aggression. In the Statute and thus far, the ICC has no police enforcement agency of its own; it therefore relies on states and other players in the international law arena to be the enforcers of its decisions and orders.' This is however not the case as not all states act in good faith when it comes to ICL and honoring of the orders of the ICC, since not all states are parties, and even if they are, not all of them necessary cooperate with the ICC, as was exhibited by South Africa when it failed to arrest Ornar Al-Bashir, an inductee of the ICC, whose arrest warrant remains unsealed, yet South Africa is a party to the Rome Statute. This paper therefore focuses on the concept of state cooperation with the ICC, especially cooperation of both state parties and non-state parties to the Rome Statute when it comes to situations in which the indicted persons are nationals of a non-state party. This paper shall limit itself to only two jurisdictions in which this state of affairs is currently existent: the Sudan and Libya, and shall assess their progress (or lack of it) in cooperation with the Court thus far.
A Dissertation submitted in partial fulfilment of the requirements for the award of the degree of Bachelor of Laws (LL.B) of Strathmore University